Properties of Gasoline Stored in Various Containers - Cheol-Hwan Jeon; Cheon-Kyu Park; Byung-Ki Na; Jae-Kon Kim (Energies, 2017)
Recently, consumers in rural areas have complained about the reduction of the octane number for gasoline stored in storage containers made of polyethylene (PE) in Korea. In addition, problems have been found in gasoline that has not been used for a long time in dual-fueled cars that use liquefied petroleum gas and gasoline at the same time. The reduction of the octane number has caused problems in the quality of fuels. To understand the fuel quality problems, the fuel properties of gasoline for automobiles were investigated in this study by storing gasoline for a long time in various simplified storage containers (tin-coated steel, PE, and polyethylene terephthalate (PET)) in a laboratory scale. For the four months of the storage period, the storage containers were kept indoors and outdoors to monitor the research octane number (RON), vapor pressure, oxidation stability, and the content of all the components to evaluate the fuel properties. In addition, the surfaces of containers were analyzed by scanning electron microscope (SEM) images of the PE storage containers that were kept outdoors under extremely harsh conditions. Depending on the storage period, some of the PE storage containers kept indoors and outdoors failed to satisfy the specification of quality standards of the gasoline as the samples with high octane numbers and low boiling points evaporated. In addition, the octane number of the gasoline in PE storage container stored indoors decreased as the content of n-paraffin and olefins having low boiling point components decreased during the storage period. The surface analysis of the PE storage containers kept indoors showed that the gasoline permeated into the surface of the containers. In this study, it has been showed that tin-coated steel material storage containers for gasoline storage are less affected by external influences than PE material storage containers and thus are more advantageous for maintaining stable fuel quality.